Bacterial population genetics in infectious disease - Robinson, D. Ashley; Falush, Daniel; Feil, Edward J. (Wiley-Blackwell, 2010)
This book is a unique synthesis of the major concepts and methods in bacterial population genetics in infectious disease, a field that is now about 35 yrs old. Emphasis is given to explaining population-level processes that shape genetic variation in bacterial populations and statistical methods of analysis of bacterial genetic data. --From publisher's description.